Pendekatan Inovasi Pembelajaran Berbasis Studi Kasus untuk Meningkatkan Keterampilan Berpikir Kritis pada Mata Kuliah Wajib Keperdataan di Prodi Hukum Universitas Bengkulu - EDYTIAWARMAN EDYTIAWARMAN; DIMAS DWI ARSO; NURHANI FITHRIAH; SITI HATIKASARI (UIN Fatmawati Sukarno Bengkulu, 2024)
This study aims to determine and analyze case study-based learning innovations that are applied to improve critical thinking skills and the obstacles faced in the implementation of case study-based learning innovations in compulsory civil affairs courses at Bengkulu University Law Study Program. The research method is conducted with empirical juridical research. The result of the research is that this case study-based learning innovation can be applied well. Students are given various kinds of cases to discuss in groups by analyzing cases and being associated with legal theories. However, there are obstacles encountered in the implementation of case study-based learning innovations in the compulsory civil affairs course at the Bengkulu University Law Study Program, namely students who do not have sufficient preparation to analyze the cases given because of their low willingness to read books and follow the development of existing cases.